Effect of Danhong injection on prognosis and inflammatory factor expression in patients with acute coronary syndrome during the perioperative period of percutaneous coronary intervention: A systematic review and meta-analysis - Li, Yuxuan; Li, Dong; Wang, Wujiao; Li, Xingxing; Li, Peng; Zhang, Yuanyuan; Lin, Qian; Li, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objectives: In China, Danhong injection (DHI) is recommended by expert consensus and is widely used in the perioperative management of patients with acute coronary syndrome (ACS). This study investigates the effect of perioperative DHI administration and the timing of DHI administration on patients with ACS undergoing percutaneous coronary intervention (PCI) by analyzing the prognosis and anti-inflammatory effects. This study summarizes the most up-to-date clinical evidence on DHI and assesses its treatment efficacy in patients with ACS. Methods: Seven databases (PubMed, Embase, Cochrane Library, SINOMED, CNKI, Wanfang, and VIP) were searched from the time of their creation to July 1, 2022. Clinical randomized controlled trials (RCTs) of DHI combined with PCI for the treatment of ACS were included. RCT quality was assessed using the Cochrane Handbook risk-of-bias tool, and STATA 17.0 was used for the Meta-analysis. Results: Thirty-three studies including 3,458 patients with ACS undergoing PCI were included in the Meta-analysis. Compared with conventional therapy, the combination of DHI and conventional therapy significantly decreased the incidence of major adverse cardiovascular events (MACEs; P<0.001) and improved the reperfusion rate (P<0.001) compared to conventional therapy alone. The serum high-sensitivity C-reactive protein (hs-CRP) and interleukin (IL)-6 levels were substantially reduced in the test group (P<0.001). In addition, the plasma levels of the myocardial injury markers and cardiac troponin T (cTnT) were declined significantly (P<0.01). Compared to the control group, DHI improved the left ventricular ejection fraction (LVEF; P<0.001) and reduced B-type natriuretic peptide (BNP; P<0.001) levels. Subgroups were established based on different timing of DHI administration: preoperative, intraoperative, and postoperative groups. The results showed that the incidence of MACEs and the reperfusion rate did not differ between the groups. Among subgroups, the postoperative group exhibited significantly lower levels of BNP, hs-CRP, and IL-6 serum, and a significantly higher LVEF level (P<0.05). Conclusion: The combination of DHI and conventional therapy results in a better therapeutic effect than that observed with conventional therapy alone in patients with ACS. To improve efficacy, postoperative initiation of DHI is recommended as a standard treatment. Further researches are needed to confirm these results.